Γ‐Secretase inhibitors suppress IL‐20‐mediated osteoclastogenesis via Notch signalling and are affected by Notch2 in vitro. (9th May 2022) - Yang, Benyi; Fu, Chaoran; Wu, Yilin; Liu, Yuanbo; Zhang, Zhen; Chen, Xin; Wu, Dongle; Gan, Ziqi; Chen, Zhengyuan; Cao, Yang
Abstract: Rheumatoid arthritis (RA) is a chronic immune disease involving the small joints, which often causes irreversible damage. In recent years, elevated interleukin 20 (IL‐20) has been observed in synovial fluid, while IL‐20 receptor overexpression has been observed in synovial cells. IL‐20 is a pleiotropic cytokine that participates in various immune diseases. Further understanding of the relationship between IL‐20 and RA can help to identify a potential clinical treatment for RA. This study demonstrated that IL‐20 can regulate osteoclast differentiation and function in a dose‐dependent manner, while influencing the expression of Notch signalling. Quantitative reverse transcription polymerase chain reaction and western blotting showed that γ‐secretase‐inhibiting drugs can reverse the effects of IL‐20. The effects of Notch2 on IL‐20‐induced osteoclastogenesis were investigated by immunofluorescence and Notch2 gene silencing via transfection of small interfering RNA; the results showed that Notch2 obviously affected the expression levels of the key protein NFATc1 and downstream osteoclastic proteins. In conclusion, we found that IL‐20 regulated the osteoclastogenesis in a dose‐dependent manner via Notch signalling, primarily by means of Notch2 activity. This study may help to find new targets for RA treatment.